A SYSTEM DYNAMICS MODEL TO ANALYSE THE ENVIRONMENTAL PROBLEM AT CONSTRUCTION SITE - Haron, Fatin Fasehah; Hawari, Nurul Nazihah (Journal of Technology Management and Business, 2018)
This study develops a system dynamics model at a construction site to analyse the impact of environmental problem. Construction sites may cause damages to the environment, and interference in the daily lives of residents. A proper environmental management system must be used to reduce pollution, enhance bio-diversity, conserve water, respect people and their local environment, measure performance and set targets for the environment and sustainability. This study investigates the damaging impact normally occur during the construction stage. Environmental problem will cause costly mistake in project implementation, either because of the environmental damages that are likely to arise during project implementation. Thus, findings from this study has helped in significantly reducing the damaging impact towards environment, and improve the environmental management system performance at construction site.Keywords: System dynamics, environmental problem, construction, environmental management system, damaging impact